2000
DOI: 10.1074/jbc.m002206200
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Excision Repair of the 5 S Ribosomal RNA Gene Assembled into a Nucleosome

Abstract: A-175-base pair fragment containing the Xenopus borealis somatic 5 S ribosomal RNA gene was used as a model system to determine the effect of nucleosome assembly on nucleotide excision repair (NER) of the major UV photoproduct (cyclobutane pyrimidine dimer (CPD)) in DNA. Xenopus oocyte nuclear extracts were used to carry out repair in vitro on reconstituted, positioned 5 S rDNA nucleosomes. Nucleosome structure strongly inhibits NER at many CPD sites in the 5 S rDNA fragment while having little effect at a few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
36
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 44 publications
5
36
0
Order By: Relevance
“…5B and TABLE TWO). This result is similar to earlier results from our laboratory for CTDs facing out near the dyad center of nucleosomes (18,37). What is more, DNA with CTD-IN (facing toward the histones) is repaired ϳ3-fold more slowly than free DNA when bound to nucleosomes ( Fig.…”
Section: Ctd Repair Rates With Nuclear Extracts Fromsupporting
confidence: 91%
“…5B and TABLE TWO). This result is similar to earlier results from our laboratory for CTDs facing out near the dyad center of nucleosomes (18,37). What is more, DNA with CTD-IN (facing toward the histones) is repaired ϳ3-fold more slowly than free DNA when bound to nucleosomes ( Fig.…”
Section: Ctd Repair Rates With Nuclear Extracts Fromsupporting
confidence: 91%
“…With Xenopus nuclear extracts, the nucleotide excision repair rates of rotationally positioned CPDs were only 2-3 times lower in nucleosomes and no more than 1.5-fold greater when a CPD was positioned away from the histone surface when compared with against the surface (41). In an earlier study with a 5S rRNA gene, no correlation was observed with rotational positioning of the CPD (45).…”
mentioning
confidence: 78%
“…: 509-335-1948; Fax: 509-335-9688; E-mail: reevesr@wsu.edu. 5 The abbreviations used are: NER, nucleotide excision repair; HMG, high mobility group; CPD, cis-syn cyclobutane pyrimidine dimer; nt, nucleotide; PRRII, positive regulatory region II; IL-2R␣, interleukin-2 receptor ␣-subunit; EMSA, electrophoretic mobility shift assay; HA, hemagglutinin; T4 endo V, T4 endonuclease V. …”
mentioning
confidence: 99%
“…In most organisms, DNA helix-distorting bulky lesions are repaired by nucleotide excision repair (NER) 5 involving the excision and replacement of 24 -32 nt of the damaged DNA strand (1). Many factors, such as (a) the type of DNA damage, (b) the DNA sequence surrounding the lesion, (c) the position in chromatin, and (d) the interactions with DNAbinding proteins, are known to affect the efficiency of NER (2)(3)(4).…”
mentioning
confidence: 99%
See 1 more Smart Citation